Sejarah dan Arsitektur Islam Sigi Heku di Kota Ternate - Jamain Warwefubun (Jurnal Tamaddun, 2023)
This study aims to determine the history of Sigi Heku and Islamic architecture in the city of Ternate, Nort Maluku Province. The research method used is the historical method which relies on four steps, namely: heuristics, criticism, interpretation and historiography. The result showed that Sigi means mosque and Heku means haka, hako, by kolano or Sultan. Sigi Heku was formed in 1304 by the fifth Sultan og Kumala Ngara Malamo Sirajul Mulki Amirul Muminin Maulana Iskandar Kaicil Muhammad Abdullah Bin Khadir Syah at the current Kadaton Fowaro Madiahi (Foramadiahi). Sigi Heku was first buil ini 1690 by the 33rd Sultan Sirajul Mulki Amirul Muâ€™minin Maulana Iskandar Amiruddin Julkarnain Syah, 12 soa (surname) located ini Siko â€œAl-Awwabinâ€ means the Sigi Heku was built at the beginning. This Sultanate mosque has a very distinctive architecture. Unique. Unlike todayâ€™s mosque wjich have domes. This mosque is inthe form of a pyramid with 6 steps, has a gate, the firstentrance, and is four square in shape, with seven layers.